1989
DOI: 10.1177/070674378903400712
|View full text |Cite
|
Sign up to set email alerts
|

Admitting Whole Families: An Alternative to Residential Care

Abstract: This paper is an examination of the effectiveness of a programme (described in detail elsewhere) designed to admit whole families for short-term intensive assessment and treatment. The goals of this programme are to eliminate residential care for symptomatic children who are admitted with their families to this service, to decrease the length of stay of the symptomatic child in residential treatment, if this is required following admission of the whole family to this unit, and to provide these services at cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Since this is an expensive treatment method it must be thoroughly evaluated. Some evaluation studies of different size, design and ambition have been made (Johnson and Savage, 1967;Abroms et al, 1971;Ro-Trock et al, 1977;Ringstad and Spurkland, 1978;Churven and Durrant, 1983;Dydyk et al, 1989;Larsen and Eldrup, 1989) showing the model's effectiveness. In Sweden there are a number of minor evaluation studies (Braaf and Hedlund, 1981;Sundelin et al, 1991;Hansson et al, 1992;Lindberg, 1993;Nerström-Bjerre, 1993;Johansson, 1995;Sköld and Österholm, 1995;Abrahamsson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Since this is an expensive treatment method it must be thoroughly evaluated. Some evaluation studies of different size, design and ambition have been made (Johnson and Savage, 1967;Abroms et al, 1971;Ro-Trock et al, 1977;Ringstad and Spurkland, 1978;Churven and Durrant, 1983;Dydyk et al, 1989;Larsen and Eldrup, 1989) showing the model's effectiveness. In Sweden there are a number of minor evaluation studies (Braaf and Hedlund, 1981;Sundelin et al, 1991;Hansson et al, 1992;Lindberg, 1993;Nerström-Bjerre, 1993;Johansson, 1995;Sköld and Österholm, 1995;Abrahamsson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the problem of identifying a child as the problem family member, some programmes advocate the admission of the entire family for therapy (e.g. Dydyk, French, Gertsman and Morrison, 1989). Such an approach clearly identifies the family as the target for intervention, minimising the blame associated with individual family members.…”
Section: Family Admission Into Residential Treatmentmentioning
confidence: 99%
“…It was also found to be cost effective for most of the studies on mental health, psychosomatic, and relational disorders. We note that family therapy was found both cheaper and more effective than treatment as usual for patients with asthma (34) and patient with psychosomatic disorders (22), and it was found cheaper and with equal effectiveness than the comparator for adolescents with symptomatic behaviours (35) and relational disorders (33). An exception to the cost effectiveness of family-based therapy for mental health disorders is the study on clinically anxious children (19), which showed that family CBT compared with individual CBT was of equal cost and effectiveness, but concluded that individual CBT had the highest probability of being cost effective in both cost per anxiety-free child and cost per QALY when modelling the CEA.…”
Section: Is Family Therapy Cost Effective?mentioning
confidence: 99%
“…Finally, the study on asthma used the reduction in asthma symptoms as a health outcome (34). Some studies used health care use and the reduction in hospital length of stay as measures of effectiveness (22,35).…”
Section: Design Of Interventionsmentioning
confidence: 99%